Association between physiological stress and skin temperature response after a half marathon. (1st April 2019) - Pérez-Guarner, Alejandro; Priego-Quesada, Jose Ignacio; Oficial-Casado, Fran; Cibrián Ortiz de Anda, Rosa Maria; Carpes, Felipe P; Palmer, Rosario Salvador
Abstract: Objective : The objective of this study was to determine the association between skin temperature response and the physiological stress after a half marathon. Approach : Seventeen runners were measured 48 h before, 24 h before, 24 h after and 48 h after completing a half marathon. The measurements on each day of testing included blood markers (creatine kinase [CK] and glutamate oxaloacetate transaminase [GOT]), perception of pain and fatigue (using a visual analogue scale), skin temperature (using infrared thermography), and jump performance (using countermovement jump test). Main results : CK ( p    <  0.001 and ES  =  2.1), GOT ( p    =  0.04 and ES  =  1.3), and perception of fatigue and pain ( p    <  0.001 and ES  >  1.0) increased 24 h after the half marathon, whereas jump performance decreased ( p    <  0.01 and ES  =  0.4). No increase of skin temperature was observed in the tests after the competition and no regression model was able to predict physiological stress using skin temperature. Only a bivariate correlation was observed between the 24 h variation (pre—24 h) of CK and the skin temperature of the posterior upper limb ( p    =  0.04 and r   =  0.5), and between the 48 h variation (pre—48 h) of pain perceived and the skin temperature of the knee ( p    <  0.01 and r   =  0.6). Significance : In conclusion, follow-up on basal skin temperatures does not seem to be an adequate method to detect physiological stress after a half marathon. In line with the observed results, we recommend caution when interpreting peaks in basal skin temperature in field sports assessments.